2021
DOI: 10.1108/mf-10-2020-0535
|View full text |Cite
|
Sign up to set email alerts
|

Forestry insurance preference among tree growers in the Ashanti Region of Ghana: a tobit and multi-nomial regression approach

Abstract: PurposeThe study analyses the preference for forestry insurance amongst tree growers in the Ashanti Region of Ghana. Specifically, the authors examine the factors influencing the amount of forestry insurance and the choice for forestry insurance types.Design/methodology/approachA total of one hundred and seventy (170) tree growers were sampled for the study. The tobit model, multi-nomial regression and Kendall's tau were employed to analyse the factors affecting the amount for forestry insurance, the choice fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…The first articles in the database are [45] and [47]. However, the literature also covers other countries such as Spain [23], Italy [25], China [21,29,36], Sweden [44], Slovakia [8,46], Germany [16,33], Ghana [38], Brazil [24,40], Portugal [17], Honduras [42,43], Japan [50], France [19,22,30], Switzerland [35,53] and New Zealand [6]. At the continental level, 13 articles related to Europe, 4 to Asia, 9 to North America, 4 to South America, 1 to Oceania and 1 to Africa.…”
Section: The Countries Where Forest Insurance Is An Issue: Europe ...mentioning
confidence: 99%
“…The first articles in the database are [45] and [47]. However, the literature also covers other countries such as Spain [23], Italy [25], China [21,29,36], Sweden [44], Slovakia [8,46], Germany [16,33], Ghana [38], Brazil [24,40], Portugal [17], Honduras [42,43], Japan [50], France [19,22,30], Switzerland [35,53] and New Zealand [6]. At the continental level, 13 articles related to Europe, 4 to Asia, 9 to North America, 4 to South America, 1 to Oceania and 1 to Africa.…”
Section: The Countries Where Forest Insurance Is An Issue: Europe ...mentioning
confidence: 99%
“…The result is suggestive that cabbage producers are economically active. Accordingly, Mensah et al (2021) indicated that the age cohort for Ghana's economically active age ranges 15-64 years implying that, cabbage producers are willing and able to work assiduously for ultimate profit. More so, cabbage production is coupled with that of tomato in the study site which reflects their sense of youthful exuberance.…”
Section: Trade Credit For Cabbage Producersmentioning
confidence: 99%